Method for preparing alpha, beta-unsaturated carbonyl compound
By using a molecular sieve catalyst with a skeleton with a variety of metal elements, the aldol condensation reaction between carbonyl compounds and formaldehyde sources was synergistically catalyzed, and the problem of low conversion of methyl propionate in existing catalysts was solved, thus achieving efficient preparation of methyl methacrylate and having good industrial application prospects.
Patent Information
- Application Number
- CN202311119006.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
In the preparation of methyl methacrylate, the conversion rate of methyl propionate is low, which affects the selectivity of the product and industrial application.
Molecular sieve with a skeleton with a variety of metal elements as catalysts are used to catalyze the aldol condensation reaction between the carbonyl compound and the formaldehyde source in the presence of alkanol to form α,β-unsaturated carbonyl compound.
It improves the conversion rate of methyl propionate and the selectivity of methyl methacrylate, is simple to operate and has good industrial application prospects.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of aldol condensation, and in particular, to a method for preparing an α,β-unsaturated carbonyl compound. Background Art
[0002] Methyl methacrylate (MMA) is an important organic chemical raw material, mainly used to produce polymethyl methacrylate) and acrylic resin materials. It is also widely used in the manufacture of other resins, plastics, coatings, adhesives, lubricants, wetting agents, glazing agents, printing and dyeing auxiliaries and insulating filling materials.
[0003] It is known that the most effective methyl propionate and formaldehyde aldol condensation catalyst is a kind of silica as the main carrier, cesium as the main active component of the supported catalyst, researchers have carried out a large number of studies and modifications on the catalyst, CN112675830A modifies the carrier silica to extend the life of the catalyst, with foam porous silica as the carrier, loading cesium metal element. The catalyst is made to have excellent water resistance, anti-carbon deposition performance and long-term activity stability, and is suitable for the industrial application of methyl propionate and formaldehyde to prepare methyl methacrylate through aldol condensation. Although the life of the catalyst is improved, there is still a problem of low conversion rate of methyl propionate. CN103551148B improves selectivity by adding an active additive, and the main active ingredient includes one or more of the oxide or salt of Cs, and the active additive is one or more of the oxide or salt of Sb, Nb, Ag, Al, and Zr, and the carrier includes SiO2 and a carrier additive. Although the product selectivity is improved, the conversion rate of methyl propionate is also low.
[0004] In order to improve the performance of the catalyst, researchers have developed other catalysts. Wierzchowsky and Zatorski, Catalysis Letters 9 (1991), pages 411 to 414 recorded the aldol condensation of formaldehyde and methyl propionate prepared in situ in the gas phase by various zeolite catalysts, the conversion of methyl propionate was less than 20%, and the selectivity of methyl methacrylate was as high as 74.1%. Mamoru Ai reported in Bull.Chem.Soc.Jpn., 63, 3722-3724 (1990) that V-Si-P ternary oxide was used as a catalyst in the reaction of methyl propionate and formaldehyde aldol condensation to prepare methyl methacrylate. The molar ratio of the reaction raw materials methyl propionate, formaldehyde, and methanol was 1:1:1, the reaction temperature was 320°C, the atomic ratio of V-Si-P ternary oxide was 1:16:3.2, the conversion of methyl propionate was about 35%, and the total yield of methyl methacrylate and methacrylic acid was 53 mol%.
[0005] Although many methods for preparing methyl methacrylate have been developed, due to the low catalytic activity of the catalyst, there is still a need to develop an improved method for preparing methyl methacrylate from a formaldehyde source and methyl propionate as raw materials. Summary of the invention
[0006] The purpose of the present disclosure is to provide a method for preparing an α,β-unsaturated carbonyl compound, which uses a molecular sieve with a framework of multiple metal elements as a catalyst, and can cause the carbonyl compound to undergo an aldol condensation reaction with a formaldehyde source in the presence of an alkanol to generate an α,β-unsaturated carbonyl compound.
[0007] In order to achieve the above-mentioned object, the present invention discloses a method for preparing an α,β-unsaturated carbonyl compound, the method comprising: contacting a mixed stream containing a carbonyl compound, a formaldehyde source and an alkanol with a catalyst and performing an aldol condensation reaction, wherein the carbonyl compound comprises an acid or an ester, and the catalyst comprises a molecular sieve having a metal element; the metal element comprises a skeleton metal element and a non-skeleton metal element, and the skeleton metal element comprises a first skeleton metal element and a second skeleton metal element; based on the total molar number of silicon elements in the molecular sieve, the content of the skeleton metal element is 0.5-5 mol%, and the non-skeleton metal element is 0.5-10 mol%. The content of metal elements is 0 to 15 mol %; the molar ratio of the non-framework metal elements to the framework metal elements is (0 to 30):1, the molar ratio of the first framework metal elements to the silicon element is (0.003 to 0.2):1, and the molar ratio of the second framework metal elements to the silicon element is (0.001 to 0.2):1; wherein the first framework metal element is selected from one or more of Ti, Zn, V, Nb and Ta, and the second framework metal element is selected from one or more of Sn, Zr and Fe; the content of metal elements is calculated as metal oxides, and the content of silicon elements is calculated as SiO2.
[0008] Optionally, the first framework metal element is Ti; and the second framework metal element is Zr or Sn.
[0009] Optionally, the non-framework metal element is selected from one or more of Ti, Sn, Zr, Fe, Zn, V, Nb and Ta; based on the total molar number of silicon elements in the molecular sieve, the content of the framework metal element is 1.5-5 mol%, preferably 2-4 mol%; the content of the non-framework metal element is 0-10 mol%, preferably 0-4 mol%; the molar ratio of the non-framework metal element to the framework metal element is (0-10):1, preferably (0-5):1, more preferably (0-2):1; The molar ratio of the first framework metal element to the silicon element is (0.005-0.2):1, preferably (0.005-0.1):1, more preferably (0.01-0.02):1, and further preferably (0.01-0.015):1; the molar ratio of the second framework metal element to the silicon element is (0.005-0.2):1, preferably (0.005-0.1):1, more preferably (0.005-0.02):1, and further preferably (0.01-0.015):1.
[0010] Optionally, the total acid content of B acid of the catalyst measured by pyridine adsorption infrared method at 50°C is 50 μmol·g -1 Below, preferably 5 μmol·g -1 Below, more preferably 0 μmol·g -1 ; L acid total acid content is 50~1000μmol·g -1 , preferably 500 to 900 μmol·g -1 , more preferably 600 to 850 μmol·g -1 .
[0011] Optionally, the carbonyl compound has a structure as shown in the following formula (1):
[0012] Formula (1), the formaldehyde source is selected from one or more of formaldehyde, trioxymethylene and polyoxymethylene; the polyoxymethylene has a structure as shown in the following formula (2): R4-O-(CH2-O) i -R5 formula (2); wherein R1 to R2 are independently selected from one or more of hydrogen, halogen groups, alkyl groups with 1 to 12 carbon atoms, substituted or unsubstituted aryl groups with 6 to 14 carbon atoms, and substituted or unsubstituted cycloalkyl groups with 3 to 12 carbon atoms; R3 is selected from one or more of hydrogen or alkyl groups with 1 to 12 carbon atoms; R4 to R5 are independently selected from one or more of alkyl groups with 1 to 12 carbon atoms, substituted or unsubstituted aryl groups with 6 to 14 carbon atoms, and substituted or unsubstituted cycloalkyl groups with 3 to 12 carbon atoms, and at most one of said R4 to R5 is selected from hydrogen; i is selected from any integer from 1 to 100;
[0013] Preferably, the halogen group is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine; the alkyl group having 1 to 12 carbon atoms is selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl, preferably methyl; the unsubstituted aryl group is selected from one or more of phenyl, naphthyl, anthracenyl and phenanthryl, wherein the substituent on the substituted aryl group is selected from alkyl groups having 1 to 8 carbon atoms, preferably methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl. More preferably, the substituted or unsubstituted aryl group having 6 to 14 carbon atoms is selected from one or more of phenyl, benzyl, propylphenyl and butylphenyl, and is further preferably phenyl or benzyl; the unsubstituted cycloalkyl group is selected from one or more of cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; the substituent on the substituted cycloalkyl group is selected from an alkyl group having 1 to 9 carbon atoms, and is preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms is selected from one or more of cyclopentyl, cyclohexyl and cycloheptyl.
[0014] Optionally, the molar ratio of the carbonyl compound to the formaldehyde source is (0.3-10):1, preferably (0.3-8):1, and more preferably (0.3-5):1; the molar ratio of the alkanol to the carbonyl compound is (0.2-5):1, preferably (0.3-3):1, and more preferably (1-3):1; the alkanol is selected from alcohols having 1 to 6 carbon atoms, preferably one or more of methanol, ethanol and tert-butanol, and more preferably methanol.
[0015] Optionally, the reaction temperature is 200-500°C, preferably 280-450°C, more preferably 300-400°C; the reaction time is 1-24h, preferably 4-12h; and the pressure is 0.01-2.0MPa, preferably 0.5-2.0MPa.
[0016] Optionally, the aldol condensation reaction is carried out in a reactor, the reactor is a fixed bed reactor, and the mass liquid hourly space velocity of the reaction is 0.1 to 4.0 h / min based on the total volume of the mixed stream. -1 , preferably 0.1 to 2.5h -1 , more preferably 0.1 to 1.2 h -1; Alternatively, the reactor is a fluidized bed reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (1-200):1, preferably (1-50):1; Alternatively, the reactor is a kettle reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (20-200):1, preferably (10-50):1.
[0017] Optionally, the reaction is carried out in an inert atmosphere and / or an oxygen-containing compound atmosphere, wherein the inert atmosphere includes one or more of nitrogen, helium and argon, and the oxygen-containing compound atmosphere includes carbon monoxide and / or carbon dioxide.
[0018] Optionally, the molecular sieve is one or more selected from MFI type molecular sieve, MEL type molecular sieve, BEA type molecular sieve, MWW type molecular sieve, FAU type molecular sieve and MOR type molecular sieve, preferably one or more selected from MFI type molecular sieve, MEL type molecular sieve and BEA type molecular sieve.
[0019] Through the above technical scheme, the present disclosure uses a molecular sieve with a framework having multiple metal elements as a catalyst, wherein the multiple framework metal elements have a synergistic effect, and can synergistically catalyze the aldol condensation reaction of carbonyl compounds and formaldehyde sources, and obtain high-purity α,β-unsaturated carbonyl compounds. Compared with the prior art, the method disclosed in the present disclosure is simple to operate, has a high raw material conversion rate and product selectivity, and has good industrial application prospects.
[0020] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0022] Figure 1 is the UV-visible spectrum of the catalyst 1 prepared in Preparation Example 1 of the present disclosure;
[0023] Figure 2 is the pyridine acid infrared spectrum of catalyst 1 prepared in Preparation Example 1 of the present disclosure;
[0024] Figure 3 It is the UV-visible spectrum of comparative catalyst 3 prepared in comparative example 3 of the present disclosure. DETAILED DESCRIPTION
[0025] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0026] The present disclosure provides a method for preparing an α,β-unsaturated carbonyl compound, the method comprising: contacting a mixed stream comprising a carbonyl compound, a formaldehyde source and an alkanol with a catalyst and performing an aldol condensation reaction, wherein the carbonyl compound comprises an acid or an ester, and the catalyst comprises a molecular sieve having a metal element; the metal element comprises a skeleton metal element and a non-skeleton metal element, and the skeleton metal element comprises a first skeleton metal element and a second skeleton metal element; based on the total molar number of silicon elements in the molecular sieve, the content of the skeleton metal element is 0.5-5 mol %, and the content of the non-skeleton metal element is 0-1 5 mol %; the molar ratio of the non-framework metal element to the framework metal element is (0-30):1, the molar ratio of the first framework metal element to the silicon element is (0.003-0.2):1, and the molar ratio of the second framework metal element to the silicon element is (0.001-0.2):1; wherein the first framework metal element is selected from one or more of Ti, Zn, V, Nb and Ta, and the second framework metal element is selected from one or more of Sn, Zr and Fe; the content of metal elements is calculated as metal oxides, and the content of silicon element is calculated as SiO2, wherein the silicon element includes all silicon in the molecular sieve.
[0027] The skeleton metal element disclosed in the present invention refers to a metal element located in the molecular sieve lattice framework and replacing a part of the silicon atoms in the molecular sieve lattice framework, and the non-skeleton metal element refers to a metal element located in the molecular sieve pores and existing in the form of an octahedral oxide. The tetracoordinated silicon element on the molecular sieve framework of the present invention is replaced by a part of the skeleton metal element, but the molecular sieve still maintains the original topological structure. The content of the metal element in the molecular sieve can be measured by the conventional XRF method in the art, and the content of the skeleton metal element and the non-skeleton metal element in the molecular sieve can be measured by ultraviolet visible spectroscopy (UV-Vis). For example, when using UV-visible spectroscopy to analyze the titanium content in molecular sieves, it is generally believed that the absorption peak appearing near a wavelength of 210 nm is the characteristic peak of the framework tetracoordinate titanium species (Stanislaw, Dzwigaj, Yannick, et al. [J]. The Journal of Physical Chemistry C, 2013, 117 (24): 12552-12559.); the absorption peak appearing near a wavelength of 270 nm is the "TiO6" species. "TiO6" is in a hydrated state, one or two water moles or hydroxyl groups will form a stable complex with the framework tetracoordinate Ti position, and their oxygen coordination will be extended from the 4th position to the 5th or 6th position. This form of titanium species is also defined as framework titanium (Q Guo, K Sun, Z Feng, et al. A Thorough Investigation of the Active Titanium Species in TS-1 Zeolite by In Situ UV Resonance Raman Spectroscopy [J]. Chem. Eur. J. 2012). The absorption peak appearing near the wavelength of 330nm is the characteristic peak of the non-framework octahedral metal oxide, namely the anatase crystal titanium species (Xiong G, Cao Y, Guo Z, et al. Physical Chemistry Chemical Physics, 2015, 18 (1): 190-196). When using UV-visible spectroscopy to analyze the states of different tin species in molecular sieves, it is generally believed that the absorption peak appearing near the wavelength of 205±3nm is the characteristic peak of the framework tetracoordinated tin species; the absorption peak appearing near the wavelength of 283±3nm is the characteristic peak of the non-framework hexacoordinated tin species (Journal of Molecular Catalysis A: Chemical, 105 (1996) 149-158). When using UV-visible spectroscopy to analyze the states of different zirconium species in molecular sieves, it is generally believed that the absorption peak appearing near the wavelength of 190±5nm is the characteristic peak of the framework tetracoordinated zirconium species, and the absorption peak appearing near the wavelength of 260±3nm is the characteristic peak of the non-framework hexacoordinated zirconium species.
[0028] The inventors of the present disclosure have found in their research that the use of molecular sieves with multiple metal elements in the framework as catalysts, wherein the multiple framework metal elements have a synergistic effect, can synergistically catalyze the aldol condensation reaction of carbonyl compounds and formaldehyde sources, and obtain high-purity α, β-unsaturated carbonyl compounds. Compared with the prior art, the method disclosed in the present disclosure is simple to operate, has a high raw material conversion rate and product selectivity, and has good industrial application prospects.
[0029] In one embodiment of the present disclosure, the first framework metal element is Ti; the second framework metal element is Zr or Sn. In the above embodiment, framework titanium is preferentially introduced into the molecular sieve framework, because the Lewis acid acidity of titanium is relatively weak, titanium is first introduced to occupy the framework position, and the amount of other metal elements with relatively strong Lewis acid acidity is reduced, and the acid amount of Lewis acid is reasonably adjusted, which is beneficial to improving the conversion rate of methyl propionate and the yield of methyl methacrylate.
[0030] In one embodiment of the present disclosure, the non-framework metal element is selected from one or more of Ti, Sn, Zr, Fe, Zn, V, Nb and Ta; in a preferred embodiment, based on the total molar number of silicon elements in the molecular sieve, the content of the framework metal element is 1.5-5 mol%, preferably 2-4 mol%; the content of the non-framework metal element is 0-10 mol%, preferably 0-4 mol%; the molar ratio of the non-framework metal element to the framework metal element is (0-10):1, preferably (0-5):1, more preferably Selected as (0~2):1; the molar ratio of the first framework metal element to the silicon element is (0.005~0.2):1, preferably (0.005~0.1):1, more preferably (0.01~0.02):1, and further preferably (0.01~0.015):1; the molar ratio of the second framework metal element to the silicon element is (0.005~0.2):1, preferably (0.005~0.1):1, more preferably (0.005~0.02):1, and further preferably (0.01~0.015):1.
[0031] In one embodiment of the present disclosure, the total acid content of the catalyst measured by pyridine adsorption infrared method at 50°C is 50 μmol·g -1 Below, preferably 5 μmol·g -1 Below, more preferably 0 μmol·g -1 ; L acid total acid content is 50~1000μmol·g -1 , preferably 500 to 900 μmol·g -1 , more preferably 600 to 850 μmol·g -1In the above embodiment, the catalytic activity of the catalyst can be further improved by selecting a preferred acid strength. The pyridine adsorption infrared spectrum is 1540cm -1 The peak reflects the B acid characteristics of the molecular sieve, at 1450±5cm -1 The peak at reflects the L-acid characteristic of the molecular sieve. The B-acid characteristic is provided by other impurity metal elements of the molecular sieve, such as metallic aluminum, and the L-acid characteristic is provided by the framework metal elements.
[0032] In one embodiment of the present disclosure, the carbonyl compound has a structure as shown in the following formula (1): Formula (1), the formaldehyde source is selected from one or more of formaldehyde, trioxymethylene and polyoxymethylene; the polyoxymethylene has a structure as shown in the following formula (2): R4-O-(CH2-O) i -R5 formula (2); wherein R1~R2 are each independently selected from one or more of hydrogen, a halogen group, an alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted aryl group having 6 to 14 carbon atoms, and a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms; R3 is selected from one or more of hydrogen or an alkyl group having 1 to 12 carbon atoms; R4~R5 are each independently selected from one or more of an alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted aryl group having 6 to 14 carbon atoms, and a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms, and at most one of said R4~R5 is selected from hydrogen; i is selected from any integer from 1 to 100.
[0033] In a preferred embodiment, the halogen group is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine; the alkyl group having 1 to 12 carbon atoms is selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl, preferably methyl; the unsubstituted aryl group is selected from one or more of phenyl, naphthyl, anthracenyl and phenanthryl, wherein the substituent on the substituted aryl group is selected from alkyl groups having 1 to 8 carbon atoms, preferably methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and More preferably, the substituted or unsubstituted aryl group having 6 to 14 carbon atoms is selected from one or more of phenyl, benzyl, propylphenyl and butylphenyl, and is further preferably phenyl or benzyl; the unsubstituted cycloalkyl group is selected from one or more of cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; the substituent on the substituted cycloalkyl group is selected from an alkyl group having 1 to 9 carbon atoms, and is preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms is selected from one or more of cyclopentyl, cyclohexyl and cycloheptyl.
[0034] In the present disclosure, "substituted or unsubstituted aryl" refers to an aryl with a substituent or an unsubstituted aryl, and a substituted aryl may be one or more hydrogen atoms in the aryl replaced by a substituent; "substituted or unsubstituted cycloalkyl" refers to a cycloalkyl with a substituent or an unsubstituted cycloalkyl, and a substituted cycloalkyl may be one or more hydrogen atoms in the cycloalkyl replaced by a substituent; the number of carbon atoms of a substituted or unsubstituted group refers to the total number of carbon atoms. For example, if the aryl group is selected from a substituted phenyl group having 10 carbon atoms, the total number of carbon atoms of the phenyl group and the substituents thereon is 10.
[0035] In a preferred embodiment, the formaldehyde source is selected from one or more of formaldehyde, trioxymethylene, formaldehyde benzyl alcohol hemiacetal and dimethanol formal, more preferably formaldehyde.
[0036] In the present disclosure, the aldol condensation product also contains other components in addition to the α,β-unsaturated carbonyl compound, for example, the aldol condensation product contains unreacted carbonyl compounds, formaldehyde sources, and / or contains decomposition products of carbonyl compounds and decomposition products of formaldehyde sources such as propionic acid and CO; based on the total weight of the aldol condensation product, the content of other components is 2 to 7 weight %.
[0037] In one embodiment of the present disclosure, the molar ratio of the carbonyl compound to the formaldehyde source is (0.3-10):1, preferably (0.3-8):1, and more preferably (0.3-5):1; the molar ratio of the alkanol to the carbonyl compound is (0.2-5):1, preferably (0.3-3):1, and more preferably (1-3):1; the alkanol is selected from alcohols having 1 to 6 carbon atoms, preferably one or more of methanol, ethanol, and tert-butyl alcohol, and more preferably methanol. In the above embodiment, by selecting an alkanol with a preferred content as a diluent, on the one hand, the carbonyl compound is prevented from undergoing a hydrolysis reaction, and on the other hand, the product is prevented from undergoing a polymerization reaction as a diluent.
[0038] In one embodiment of the present disclosure, the reaction temperature is 200-500°C, preferably 280-450°C, more preferably 300-400°C; the reaction time is 1-24h, preferably 4-12h; the pressure is 0.01-2.0MPa, preferably 0.5-2.0MPa. The method of the present disclosure does not limit the heat source, and in principle any heat source can be used.
[0039] The reaction of the present disclosure is carried out in a conventional reactor, and the present disclosure does not impose any special restrictions. In one embodiment of the present disclosure, the aldol condensation reaction is carried out in a reactor, and the reactor is a fixed bed reactor, and the mass liquid hourly space velocity of the reaction is 0.1 to 4.0 h based on the total volume of the mixed stream. -1 , preferably 0.1 to 2.5h -1 , more preferably 0.1 to 1.2 h -1 ; Alternatively, the reactor is a fluidized bed reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (1-200):1, preferably (1-50):1; Alternatively, the reactor is a tank reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (20-200):1, preferably (10-50):1. The mass liquid hourly space velocity of the reaction refers to the mass of the mixed material flow passing through a unit mass of the catalyst per unit time.
[0040] It can be understood by those skilled in the art that, depending on the different reactors used, the catalyst described in the present disclosure can be the original powder of the molecular sieve containing multiple metal elements in the framework, or it can be a shaped catalyst after the molecular sieve containing multiple metal elements in the framework is mixed and shaped with a carrier. The separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered molecular sieve containing multiple metal elements in the framework is used as the catalyst, the separation of the product and the recovery and reuse of the catalyst can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation, etc. Alternatively, the catalyst can be formed and loaded into a fixed bed reactor, and the catalyst can be recovered after the reaction is completed. Various catalyst separation and recovery methods are involved in the existing literature, which will not be described here. The specific operation mode of the reactor is well known to those skilled in the art.
[0041] In one embodiment of the present disclosure, the reaction is carried out in an inert atmosphere and / or an oxygen-containing compound atmosphere, wherein the inert atmosphere includes one or more of nitrogen, helium and argon, and the oxygen-containing compound atmosphere includes carbon monoxide and / or carbon dioxide. The atmosphere can be supplied to the reaction process of the present disclosure from the outside, or the gas can be circulated in the reaction process by means of one or more circulation steps.
[0042] In one embodiment of the present disclosure, the molecular sieve is selected from one or more of MFI type molecular sieve, MEL type molecular sieve, BEA type molecular sieve, MWW type molecular sieve, FAU type molecular sieve and MOR type molecular sieve, preferably one or more of MFI type molecular sieve, MEL type molecular sieve and BEA type molecular sieve.
[0043] In one embodiment of the present disclosure, the molecular sieve is a product of metal elements replacing part of the framework silicon of molecular sieves of various topological structures. The topological structure of the molecular sieve can be referenced from the website of the International Zeolite Association. For example, the molecular sieve can be selected from one or more of MFI type molecular sieves, MEL type molecular sieves, BEA type molecular sieves, MWW type molecular sieves, FAU type molecular sieves and MOR type molecular sieves, preferably one or more of MFI type molecular sieves, MEL type molecular sieves and BEA type molecular sieves. In one embodiment, when the skeleton metal element and the non-skeleton metal element are both Ti and Sn, the molecular sieve is a tin-titanium-silicon molecular sieve, and the tin-titanium-silicon molecular sieve is selected from one or more of MFI-type tin-titanium-silicon molecular sieve, MEL-type tin-titanium-silicon molecular sieve, BEA-type tin-titanium-silicon molecular sieve, MWW-type tin-titanium-silicon molecular sieve, FAU-type tin-titanium-silicon molecular sieve and MOR-type tin-titanium-silicon molecular sieve, MFI-type tin-titanium-silicon molecular sieve is, for example, Ti-MFI molecular sieve, MEL-type tin-titanium-silicon molecular sieve is, for example, Ti-MEL molecular sieve, BEA-type tin-titanium-silicon molecular sieve is, for example, Ti-Beta molecular sieve, MWW-type tin-titanium-silicon molecular sieve is, for example, Ti-MCM-22 molecular sieve, FAU-type tin-titanium-silicon molecular sieve is, for example, Ti-FAU molecular sieve, and MOR-type tin-titanium-silicon molecular sieve is, for example, Ti-MOR molecular sieve. Further preferably, the tin-titanium-silicon molecular sieve is an MFI-type tin-titanium-silicon molecular sieve. The source of the molecular sieve is not limited, and it can be obtained by commercial purchase or prepared by conventional technical methods in the art.
[0044] The present disclosure is further illustrated by the following examples, but the present disclosure is not limited thereto. Unless otherwise specified, the raw materials used in the examples and comparative examples of the present disclosure are purchased through commercial channels and are pure reagents.
[0045] The embodiments and comparative examples of the present disclosure adopt ultraviolet-visible spectroscopy to analyze framework metal elements and non-framework metal elements. The instrument model is Cary300 ultraviolet spectrophotometer, the manufacturer is Agilent, and the test conditions are: room temperature, normal pressure, the sample is tested after tabletting, and the scanning range is 190-800nm.
[0046] The types and contents of all metal elements and the content of silicon were determined using a ZSX100E X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan. Test conditions: The samples were pressed into tablets and tested using tungsten-palladium, with an excitation voltage of 40 kV and an excitation current of 250 mA.
[0047] The acid content of B acid and L acid was measured by 2,6-di-tert-butylpyridine adsorption infrared acid method using a Vertex 70 instrument produced by Bruker Instruments. The specific method is as follows: the catalyst is pressed into a 10 mg / cm 2The thin slice was placed in an infrared cell with a CaF2 window, first evacuated at 400°C, then lowered to 150°C to adsorb 2,6-di-tert-butylpyridine for 15 minutes, then evacuated for 1 hour, lowered to room temperature to collect spectra, and calculated the acid amounts of B acid and L acid. See Applied Catalysis A: General, 294, 2005: 92.
[0048] The composition of the reaction product was analyzed by gas chromatography, and the analysis results were quantified by external standard method. The chromatographic analysis conditions were: Agilent-6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C; column temperature was maintained at 100°C for 2 min, then increased to 200°C at a rate of 15°C / min and maintained for 3 min. FID detector, detector temperature 300°C.
[0049] The particle size unit "mesh" in the present disclosure refers to the number of holes per inch on the screen used to screen different particle sizes. For example, 20 mesh means that there are 20 holes per inch on the screen, and 20-40 mesh refers to the particle size that can pass through the 20 mesh screen and be retained by the 40 mesh screen.
[0050] The preparation examples and the preparation comparative examples are used to provide catalysts used in the examples and comparative examples.
[0051] Preparation Example 1
[0052] Tetraethyl orthosilicate (TEOS), n-butyl titanate [Ti(OBu)4], zirconium propoxide and tetrapropylammonium hydroxide (TPAOH, 26.5wt%) solution were mixed in a molar ratio of SiO2: 0.02TiO2: 0.02ZrO2: 0.36TPAOH: 35H2O, and then stirred for 15 minutes to obtain a clear liquid. Finally, water was added to the clear liquid and stirred at 348-353K for about 3 hours to obtain a clear liquid. The clear sol was then crystallized at 443K for 3 days, after which the obtained solid was filtered, washed with distilled water, dried at 373K for 5h, and then calcined at 823K for 10h to obtain Ti-Zr-MFI-1 molecular sieve raw powder, which was pressed into sheets at 20MPa pressure, and particles of 20-40 mesh (i.e., average particle size of 0.63-0.85mm) were screened as catalyst 1, denoted as C1, and its composition is shown in Table 1. The amount of TEOS used was 208.3g, the amount of Ti(OBu)4 used was 6.8g, the amount of zirconium n-propoxide used was 9.3g (70wt% n-propanol solution), the amount of TPAOH used was 286g, and the amount of water used was 417.5g.
[0053] The UV-visible spectrum of the prepared catalyst C1 is shown in Figure 1 As shown, from Figure 1It can be seen that C1 has framework metal titanium and framework metal zirconium, wherein a characteristic peak of the framework tetracoordinated titanium species appears near a wavelength of 210 nm, and a characteristic peak of the framework tetracoordinated zirconium species appears near a wavelength of 190±5 nm.
[0054] The pyridine acid infrared spectrum of catalyst C1 is as follows Figure 2 As shown, from Figure 2 It can be seen that C1 is at 1540cm -1 There is no peak at the position of C1, indicating that C1 has no B acid site and its B acid content is 0 μmol·g -1 ; at 1446cm -1 The peak at 100 μmol·g indicates that C1 has an L-acid site and its L-acid content is 810.1 μmol·g -1 , the L acid site is beneficial to improving the raw material conversion rate and product selectivity.
[0055] Preparation Example 2
[0056] The same as Preparation Example 1, the only difference is: tetrapropylammonium hydroxide solution (TPAOH, 26.5wt%) is replaced by tetrabutylammonium hydroxide solution (TBAOH, 20wt%), the amount of TBAOH is 259.5g, so that the materials are mixed according to the molar ratio of SiO2: 0.02TiO2: 0.02ZrO2: 0.20TBAOH: 35H2O to obtain Ti-Zr-MEL molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20-40 mesh (i.e., average particle size of 0.63-0.85mm) are screened as catalyst 2, denoted as C2, and its composition is shown in Table 1.
[0057] Preparation Example 3
[0058] The same as Preparation Example 1, the only difference is that zirconium n-propoxide is replaced by tin tetrachloride SnCl4·5H2O, the amount of tin tetrachloride is 7.0g, so that the materials are mixed according to the molar ratio of SiO2: 0.02TiO2: 0.02SnO2: 0.36TPAOH: 35H2O to obtain Ti-Sn-MFI molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., an average particle size of 0.63 to 0.85mm) are screened as catalyst 3, denoted as C3, and its composition is shown in Table 1.
[0059] Preparation Example 4
[0060] The same as Preparation Example 1, the only difference is: zirconium n-propoxide is replaced by ferric chloride, the amount of ferric chloride is 3.24g, so that the materials are mixed according to the molar ratio of SiO2: 0.02TiO2: 0.02Fe2O3: 0.36TPAOH: 35H2O to obtain Ti-Fe-MFI molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., the average particle size is 0.63 to 0.85mm) are screened as catalyst 4, denoted as C4, and its composition is shown in Table 1.
[0061] Preparation Example 5
[0062] 60g of BEA molecular sieve with a silicon-aluminum ratio of 11 after calcination was mixed with a 13mol / L nitric acid aqueous solution, and the mixed solution was stirred at 90°C for 24h, washed with deionized water, dried and calcined to obtain a dealuminated molecular sieve; the dealuminated molecular sieve was mixed with 5.8g of titanium tetrachloride and 7.0g of tin tetrachloride and stirred, filtered and dried, and calcined at 550°C for 3h to obtain Ti-Sn-BEA molecular sieve raw powder, which was pressed into sheets under a pressure of 20MPa, and particles of 20-40 mesh (i.e., an average particle size of 0.63-0.85mm) were screened as catalyst 5, denoted as C5, and its composition is shown in Table 1.
[0063] Preparation Example 6
[0064] The same as Preparation Example 1, the only difference is that the amount of Ti(OBu)4 used is 20.5g, the amount of zirconium n-propoxide used is 14.0g, so that the materials are mixed according to the molar ratio of SiO2: 0.06TiO2: 0.03ZrO2: 0.36TPAOH: 35H2O to obtain Ti-Zr-MFI-2 molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., the average particle size is 0.63 to 0.85mm) are screened as catalyst 6, denoted as C6, and its composition is shown in Table 1.
[0065] Preparation Example 7
[0066] The same as Preparation Example 1, the only difference is that the amount of Ti(OBu)4 used is 1.0g, the amount of zirconium n-propoxide used is 0.94g, so that the materials are mixed according to the molar ratio of SiO2: 0.003TiO2: 0.002ZrO2: 0.36TPAOH: 35H2O to obtain Ti-Zr-MFI-3 molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., an average particle size of 0.63 to 0.85mm) are screened as catalyst 7, denoted as C7, and its composition is shown in Table 1.
[0067] Preparation Example 8
[0068] The same as Preparation Example 1, the only difference is: n-butyl titanate [Ti(OBu)4] is replaced by the same molar amount of tin tetrachloride SnCl4·5H2O to obtain Sn-Zr-MFI molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20 MPa, and particles of 20 to 40 mesh (i.e., an average particle size of 0.63 to 0.85 mm) are screened as catalyst 8, denoted as C8, and its composition is shown in Table 1.
[0069] Preparation Comparative Example 1
[0070] This comparative preparation example is prepared according to the method of the document M.Ai.Applied Catalysis A: General 288 (2005) 211-215 to prepare an amorphous silica molecular sieve loaded with Ti and Zr. The specific preparation method is as follows:
[0071] The excess water in the aqueous SiO2 colloid (20%) was evaporated to obtain a silica dry gel; the dry gel was ground and sieved to obtain a solid with a size of 8 to 20 meshes. The obtained solid was calcined at 400°C for 4 hours, and then impregnated with an aqueous solution containing the required amount of titanium tetrachloride and zirconium n-propoxide (the concentration of titanium tetrachloride in the impregnation solution was 0.2 mol / L, and the concentration of zirconium n-propoxide was 0.2 mol / L). The wet gel was dried in an oven and calcined again at 400°C in an air flow for 6 hours to obtain Ti-Zr / SiO2 molecular sieve raw powder, which was pressed into sheets at a pressure of 20 MPa, and particles of 20 to 40 meshes (i.e., an average particle size of 0.63 to 0.85 mm) were screened as comparative catalyst 1, denoted as D1, and its composition is shown in Table 1.
[0072] Preparation Comparative Example 2
[0073] A measured solution of tetrapropylammonium hydroxide (TPAOH, 26.5wt%) was added to a solution of tetraethyl orthosilicate (TEOS) to obtain a liquid mixture with a pH of about 13, and then stirred for 3 hours under vigorous stirring to obtain a clear liquid, and then stirred for about 3 hours at 348-353K to obtain a sol with a chemical composition of SiO2: 0.36TPAOH: 35H2O, and then crystallized at 443K for 3 days, after which the obtained solid was filtered, washed with distilled water, dried at 373K for 5 hours, and then calcined at 823K for 10 hours to obtain a full-silicon S-MFI molecular sieve. Among them, the amount of TEOS used is 208.3g, the amount of TPAOH used is 286g, and the amount of water used is 417.5g;
[0074] 0.02 mol (3.8 g) of titanium tetrachloride and 0.02 mol (7.0 g) of tin tetrachloride were dissolved in ethanol, and then impregnated with S-MFI molecular sieve in equal volumes and dried at 110°C for 2 h. After the mixture was dried, it was placed in a muffle furnace and calcined at 400°C for 4 h to obtain the impregnated loaded D-Ti-Sn-MFI-1 molecular sieve raw powder. The molecular sieve raw powder was pressed into sheets at a pressure of 20 MPa, and particles of 20 to 40 mesh (i.e., an average particle size of 0.63 to 0.85 mm) were screened as comparative catalyst 2, denoted as D2, and its composition is shown in Table 1.
[0075] Preparation Comparative Example 3
[0076] The same as Preparation Example 1, the only difference is that the amount of Ti(OBu)4 used is 40.5g, the amount of zirconium n-propoxide used is 28.1g, so that the materials are mixed according to the molar ratio of SiO2: 0.12TiO2: 0.06ZrO2: 0.36TPAOH: 35H2O to obtain D-Ti-Zr-MFI-2 molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., the average particle size is 0.63 to 0.85mm) are screened as comparative catalyst 3, denoted as D3, and its composition is shown in Table 1.
[0077] The UV-visible spectrum of the prepared catalyst D3 is shown in Figure 3 As shown, from Figure 3 It can be seen that D3 has skeleton metal titanium, skeleton metal zirconium, non-skeleton metal titanium and non-skeleton metal zirconium, among which the characteristic peak of skeleton tetracoordinate titanium species appears near a wavelength of 210nm, the characteristic peak of skeleton tetracoordinate zirconium species appears near a wavelength of 190±5nm, the characteristic peak of non-skeleton octahedral titanium dioxide appears near a wavelength of 340nm, and the characteristic peak of non-skeleton hexacoordinate zirconium species appears near a wavelength of 260nm.
[0078] Preparation Comparative Example 4
[0079] The same as Preparation Example 1, the only difference is that the amount of Ti(OBu)4 used is 0.34g, the amount of zirconium n-propoxide used is 0.48g, so that the materials are mixed according to the molar ratio of SiO2: 0.001TiO2: 0.001ZrO2: 0.36TPAOH: 35H2O to obtain D-Ti-Zr-MFI-3 molecular sieve raw powder, the molecular sieve raw powder is pressed into tablets at a pressure of 20MPa, and particles of 20 to 40 mesh (i.e., the average particle size is 0.63 to 0.85mm) are screened as comparative catalyst 4, denoted as D4, and its composition is shown in Table 1.
[0080] Table 1
[0081]
[0082] “-” means that the species is not contained or the content of the species is 0.
[0083] The following examples and comparative examples are used to illustrate the method of preparing α,β-unsaturated carbonyl compounds by catalyzing carbonyl compounds with formaldehyde sources using different catalysts.
[0084] Example 1
[0085] The catalyst C1 prepared in Preparation Example 1 was loaded into a fixed bed reactor and preactivated. The preactivation conditions were as follows: N2 flow rate was 100 mL / min, the temperature was raised to 400°C at a rate of 2°C / min, and the temperature was kept constant at 400°C for 5 hours, and then the temperature was lowered to the required reaction temperature of 320°C in a nitrogen atmosphere. Formaldehyde, methyl propionate and methanol were fed into the bed of the reaction section through N2, wherein the reaction temperature was 320°C, the reaction time was 2 hours, the reaction pressure was 0.5 MPa, the molar ratio of formaldehyde to methyl propionate was 1:1, the molar ratio of methanol to methyl propionate was 1.5:1, and the mass liquid hourly space velocity of the reaction feed was 0.5 h based on the total amount of formaldehyde, methyl propionate and methanol. -1 The results of the aldol condensation reaction are shown in Table 2. The conversion rate of methyl propionate and the selectivity of methyl methacrylate are calculated according to the following formulas (1) to (2):
[0086]
[0087]
[0088] Embodiments 2 to 8
[0089] The aldol condensation reaction was carried out according to the method and reaction conditions of Example 1, except that the catalysts C2 to C8 prepared in Preparation Examples 2 to 8 were used to catalyze the aldol condensation reaction. The reaction results are shown in Table 2.
[0090] Example 9
[0091] The aldol condensation reaction was carried out according to the method and reaction conditions of Example 1, except that methyl propionate was replaced by the same amount of propionic acid. The reaction product was acrylic acid, the conversion rate of propionic acid was 83.5%, and the selectivity of acrylic acid was 96.0%.
[0092] Example 10
[0093] The aldol condensation reaction was carried out according to the method of Example 1. The reaction conditions were: temperature of 360°C, time of 2h, pressure of 0.5MPa, molar ratio of formaldehyde to methyl propionate of 1:5, molar ratio of methanol to methyl propionate of 1.5:1, and the mass liquid hourly space velocity of the reaction feed was 0.8h-1 based on the total amount of formaldehyde, methyl propionate and methanol. -1, the conversion rate of methyl propionate was 19.5%, and the selectivity of methyl methacrylate was 95.1%.
[0094] Comparative Examples 1 to 4
[0095] The aldol condensation reaction was carried out according to the method and reaction conditions of Example 1, except that the comparative catalysts D1 to D4 prepared in Comparative Preparation Examples 1 to 4 were used to catalyze the aldol condensation reaction. The reaction results are shown in Table 2.
[0096] Table 2
[0097]
[0098] It can be seen from the results of the above embodiments and comparative examples that the method of the present invention is used to prepare α, β-unsaturated carbonyl compounds, and the total molar number of silicon elements in the molecular sieve is used as a reference, the content of the framework metal element is 0.5-5 mol%, and the content of the non-framework metal element is 0-15 mol%; the molar ratio of the non-framework metal element to the framework metal element is (0-30):1, the molar ratio of the first framework metal element to the silicon element is (0.003-0.2):1, and the molar ratio of the second framework metal element to the silicon element is (0.001-0.2):1, which can effectively improve the conversion rate of methyl propionate and improve the selectivity of methyl methacrylate.
[0099] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0100] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0101] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing an α,β-unsaturated carbonyl compound, characterized in that: The method comprises: contacting a mixed stream comprising a carbonyl compound, a formaldehyde source and an alkanol with a catalyst and performing an aldol condensation reaction, wherein the carbonyl compound comprises an acid or an ester, and the catalyst comprises a molecular sieve having a metal element; The metal elements include skeleton metal elements and non-skeleton metal elements, and the skeleton metal elements include a first skeleton metal element and a second skeleton metal element; based on the total molar number of silicon elements in the molecular sieve, the content of the skeleton metal elements is 0.5-5 mol%, and the content of the non-skeleton metal elements is 0-15 mol%; the molar ratio of the non-skeleton metal elements to the skeleton metal elements is (0-30):1, the molar ratio of the first skeleton metal element to the silicon element is (0.003-0.2):1, and the molar ratio of the second skeleton metal element to the silicon element is (0.001-0.2):1; The first skeleton metal element is selected from one or more of Ti, Zn, V, Nb and Ta, and the second skeleton metal element is selected from one or more of Sn, Zr and Fe; the content of metal elements is calculated as metal oxides, and the content of silicon is calculated as SiO2.
2. The method according to claim 1, characterized in that: The first framework metal element is Ti; the second framework metal element is Zr or Sn.
3. The method according to claim 1, characterized in that The non-framework metal element is selected from one or more of Ti, Sn, Zr, Fe, Zn, V, Nb and Ta; Based on the total molar number of silicon elements in the molecular sieve, the content of the framework metal element is 1.5 to 5 mol%, preferably 2 to 4 mol%; the content of the non-framework metal element is 0 to 10 mol%, preferably 0 to 4 mol%; the molar ratio of the non-framework metal element to the framework metal element is (0 to 10):1, preferably (0 to 5):1, and more preferably (0 to 2):1; The molar ratio of the first framework metal element to the silicon element is (0.005-0.2):1, preferably (0.005-0.1):1, more preferably (0.01-0.02):1, and further preferably (0.01-0.015):1; the molar ratio of the second framework metal element to the silicon element is (0.005-0.2):1, preferably (0.005-0.1):1, more preferably (0.005-0.02):1, and further preferably (0.01-0.015):
1.
4. The method according to claim 1, characterized in that The total acid content of B acid of the catalyst measured by pyridine adsorption infrared method at 50°C is 50 μmol·g -1 Below, preferably 5 μmol·g -1 Below, more preferably 0 μmol·g -1 ; L acid total acid content is 50~1000μmol·g -1 , preferably 500 to 900 μmol·g -1 , more preferably 600 to 850 μmol·g -1 .
5. The method according to claim 1, characterized in that The carbonyl compound has a structure as shown in the following formula (1): The formaldehyde source is selected from one or more of formaldehyde, trioxymethylene and polyoxymethylene; the polyoxymethylene has a structure as shown in the following formula (2): R4-O-(CH2-O) i -R5 formula (2); Wherein, R1-R2 are independently selected from one or more of hydrogen, halogen groups, alkyl groups with 1-12 carbon atoms, substituted or unsubstituted aryl groups with 6-14 carbon atoms, and substituted or unsubstituted cycloalkyl groups with 3-12 carbon atoms; R3 is selected from hydrogen or alkyl groups with 1-12 carbon atoms; R4-R5 are independently selected from one or more of alkyl groups with 1-12 carbon atoms, substituted or unsubstituted aryl groups with 6-14 carbon atoms, and substituted or unsubstituted cycloalkyl groups with 3-12 carbon atoms, and at most one of R4-R5 is selected from hydrogen; i is selected from any integer from 1 to 100; Preferably, the halogen group is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine; The alkyl group having 1 to 12 carbon atoms is one or more selected from the group consisting of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl, and is preferably methyl; The unsubstituted aryl group is selected from one or more of phenyl, naphthyl, anthracenyl and phenanthrenyl, wherein the substituent on the substituted aryl group is selected from an alkyl group having 1 to 8 carbon atoms, preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted aryl group having 6 to 14 carbon atoms is selected from one or more of phenyl, benzyl, propylphenyl and butylphenyl, further preferably phenyl or benzyl; The unsubstituted cycloalkyl group is selected from one or more of cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; the substituent on the substituted cycloalkyl group is selected from one or more of alkyl groups having 1 to 9 carbon atoms, preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms is selected from one or more of cyclopentyl, cyclohexyl and cycloheptyl.
6. The method according to claim 1, characterized in that The molar ratio of the carbonyl compound to the formaldehyde source is (0.3-10):1, preferably (0.3-8):1, and more preferably (0.3-5):1; the molar ratio of the alkanol to the carbonyl compound is (0.2-5):1, preferably (0.3-3):1, and more preferably (1-3):1; The alkanol is selected from alcohols having 1 to 6 carbon atoms, preferably one or more of methanol, ethanol and tert-butanol, more preferably methanol.
7. The method according to claim 1, characterized in that The reaction temperature is 200-500° C., preferably 280-450° C., more preferably 300-400° C.; the reaction time is 1-24 h, preferably 4-12 h; and the pressure is 0.01-2.0 MPa, preferably 0.5-2.0 MPa.
8. The method according to claim 1, characterized in that: The aldol condensation reaction is carried out in a reactor, which is a fixed bed reactor. The mass liquid hourly space velocity of the reaction is 0.1 to 4.0 h based on the total volume of the mixed stream. -1 , preferably 0.1 to 2.5 hours -1 , more preferably 0.1 to 1.2 h -1 ; or, The reactor is a fluidized bed reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (1-200):1, preferably (1-50):1; or, The reactor is a kettle reactor, and the weight ratio of the mixture of the carbonyl compound and the formaldehyde source to the catalyst is (20-200):1, preferably (10-50):
1.
9. The method according to claim 1, characterized in that: The reaction is carried out in an inert atmosphere and / or an oxygen-containing compound atmosphere, wherein the inert atmosphere includes one or more of nitrogen, helium and argon, and the oxygen-containing compound atmosphere includes carbon monoxide and / or carbon dioxide.
10. The method according to claim 1, characterized in that The molecular sieve is one or more selected from MFI type molecular sieve, MEL type molecular sieve, BEA type molecular sieve, MWW type molecular sieve, FAU type molecular sieve and MOR type molecular sieve, preferably one or more selected from MFI type molecular sieve, MEL type molecular sieve and BEA type molecular sieve.
Citation Information
Patent Citations
A water-resistant catalyst for aldol condensation, its preparation method and application
CN103551148B